A study of forty eight patients with ilecoceacal mass presenting as intestinal obstruction requires surgical intervention and their outcome - Gupta, Himanshu; Anand, Sumikesh (International Surgery Journal, 2020)
Background: Intestinal obstruction is defined as obstruction of the passage of the intestine for its contents. Successful conservative treatment may leave adhesions that could cause recurrence; on the other hand, surgery may be the source of new adhesions like any other abdominal surgery. Hence, the present study was undertaken for assessing the 48 patients with ilecoceacal mass presenting as intestinal obstruction requires surgical intervention and their outcome. Methods: Of a total of 48 patients with ilecoceacal masses who presented with intestinal obstruction and underwent surgical intervention for the same. Surgical management outcome was classified as “favorable” or “unfavorable” outcome according to the retrospective secondary data extracted from their medical records. Unfavorable outcome was considered if the patient died or has one or more postoperative complications. Favorable outcome was considered if the patient was discharged alive and does not have any history of postoperative complications. Results: Abdominal pain, abdominal distension, vomiting and failure to pass faeces were the prominent presenting symptoms among intestinal obstruction patients. Favourable outcome was seen in 76 percent of the patients while unfavourable outcome was seen in 24 percent of the patients. Mortality occurred in 6 patients. Prolonged ileus was found to be present in 1 patient. Failure to wean from ventilator for more than 48 hours was seen in 2 patients. Conclusions: Surgical management had high efficacy of more than 75 percent in managing patients with intestinal obstructions. With precise technique and adequate care, complication rate can be reduced.